Governing the gold rush into emerging markets: A case study of Indonesia's regulatory responses to the expansion of Chinese-backed online P2P lending - Angela Tritto; Yujia He; Victoria Amanda Junaedi (Financial Innovation, 2020)
Peer-to-peer (P2P) lending has the potential to boost financial inclusion in emerging markets. This paper contributes to the literature on fintech governance in emerging Asian markets. It examines the case of the Indonesian government's approach in regulating the P2P lending sector using both primary interviews and secondary firmlevel data. Driven by regulation tightening in China and regulatory gaps in Indonesia, Chinese investments became the largest in this sector contributing, however, to growing risks from illegal business practices. The Indonesian government responded by creating new regulations and institutions, mitigating risks without stifling the potential for financial inclusion. We conclude a proactive approach towards monitoring and regulating emerging high-tech industries should be sought by strengthening links with industry and civil society, and through international cooperation for policy and knowledge sharing.
Keywords: 650; Fintech; P2P; Internet finance; Governance; Emerging market